2017
DOI: 10.1093/nar/gkx299
|View full text |Cite
|
Sign up to set email alerts
|

Newly characterized interaction stabilizes DNA structure: oligoethylene glycols stabilize G-quadruplexes CH–π interactions

Abstract: Oligoethylene glycols are used as crowding agents in experiments that aim to understand the effects of intracellular environments on DNAs. Moreover, DNAs with covalently attached oligoethylene glycols are used as cargo carriers for drug delivery systems. To investigate how oligoethylene glycols interact with DNAs, we incorporated deoxythymidine modified with oligoethylene glycols of different lengths, such as tetraethylene glycol (TEG), into DNAs that form antiparallel G-quadruplex or hairpin structures such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Moreover, it has also been reported that the carbohydrates stack on the ends of the DNA duplexes via CH-π interactions, stabilizing the duplexes [26]. We have also shown that the presence of linear TEG in the loop of the G-quadruplex allows adoption of a conformation suitable for CH-π interactions of TEG with a G-quartet [17]. Thus, the stabilization of G-quadruplexes by dibranched TEGs may also be due to CH-π interactions.…”
Section: Thermodynamic Analysis Of the Effects Of Teg-modified Deoxytsupporting
confidence: 54%
See 4 more Smart Citations
“…Moreover, it has also been reported that the carbohydrates stack on the ends of the DNA duplexes via CH-π interactions, stabilizing the duplexes [26]. We have also shown that the presence of linear TEG in the loop of the G-quadruplex allows adoption of a conformation suitable for CH-π interactions of TEG with a G-quartet [17]. Thus, the stabilization of G-quadruplexes by dibranched TEGs may also be due to CH-π interactions.…”
Section: Thermodynamic Analysis Of the Effects Of Teg-modified Deoxytsupporting
confidence: 54%
“…Based on a previous NMR study of the thrombin aptamer, deoxythymines in position four (T 4 ) and 13 (T 13 ) stack on a G-quartet, while deoxythymine in position seven (T 7 ) does not [19,20]. We proved that stabilization of G-quadruplexes by linear TEG-modified deoxythymines depends on the positions of incorporation; deoxythymines stacked on a G-quartet significantly increase stability, while those not stacked show almost no effect [17]. Thus, we replaced deoxythymines in the loop regions of Q1 with (2X4) or (3X4) as shown in Table 1.…”
Section: Sequence Design To Understand the Effect Of Modified Deoxythmentioning
confidence: 67%
See 3 more Smart Citations